2022
DOI: 10.3233/adr-220053
|View full text |Cite
|
Sign up to set email alerts
|

Tooth Loss Induces Memory Impairment and Glial Activation in Young Wild-Type Mice

Abstract: Background: Tooth loss is closely associated with Alzheimer’s disease (AD). Previously, we reported that tooth loss induced memory impairment in amyloid precursor protein knock-in mice by decreasing neuronal activity and synaptic protein levels and increasing glial activation, neuroinflammation, and pyramidal neuronal cell loss without altering amyloid-β levels in the hippocampus. However, the effects of tooth loss in young wild-type mice have not been explored yet. Objective: We investigated the effects of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The animal-based data seem to support an association between tooth loss and Alzheimer's disease better than the human evidence. Taslima et al [50] recently showed that tooth loss in wild-type mice is associated with increased levels of proteins activated by chronic stress, which activated microglial cells. Sakamoto et al [51] demonstrated that occlusal rehabilitation in rats improved spatial memory and increased neuron density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The animal-based data seem to support an association between tooth loss and Alzheimer's disease better than the human evidence. Taslima et al [50] recently showed that tooth loss in wild-type mice is associated with increased levels of proteins activated by chronic stress, which activated microglial cells. Sakamoto et al [51] demonstrated that occlusal rehabilitation in rats improved spatial memory and increased neuron density.…”
Section: Discussionmentioning
confidence: 99%
“…Animal experiments have shown an association between tooth loss and cognitive impairment [46][47][48][49][50]. Que et al found that tooth loss induces memory impairment and neuronal cell loss in a mouse model [47].…”
Section: Animal Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that loss of teeth can lead to decreased activation and degenerative changes in hippocampus 24–27 . As occlusal support loss must be accompanied by reduction and loss of masticatory activation, we assume that not only the ascending nerve pathway, but also the hippocampus will show negative plasticity changes, which may explain the memory loss.…”
Section: Introductionmentioning
confidence: 87%
“…Furthermore, the number of astrocytes in the hippocampus of experimental animal models has been shown to be susceptible to masticatory disorders [ 20 ]. Taslima et al (2021) [ 26 ] showed that tooth extraction in AD model mice resulted in an increase in the number of hippocampal astrocytes. Astrocytic changes linked to morphological complexity in the DG molecular layer and changes in laminar distribution in CA1 were also observed, mainly when reduced activity was associated with aging and a depleted environment [ 17 , 27 ].…”
Section: Introductionmentioning
confidence: 99%